Rights issues on the stock exchange of Singapore - Phua, Chee Khoon (2015)
This empirical study is to investigate the validity of the Efficient Market Hypothesis in respect of rights issues coming onto the Singapore Stock Market, for the 2 1/2 years from January 1991 to June 1993 and to show how rights issues could be particularly beneficial to shareholders. For this purpose all 23 companies with 26 stocks were analyzed for price movements from just prior to the announcement of, to the relevant ex-all dates, for these rights issues. Every file for each of the 23 companies, maintained at the Stock Exchange Library, were examined for announcements, events and data relevant to the companies at the time of such rights tssues. Findings revealed that when companies announce rights issues, the majority of them (i.e. 61.5%) registered an immediate increase in their stock prices, ranging from, 0. 6% to 10%. This implies that the Singapore Stock Market exhibits a semi-strong form of Efficiency in that stock prices react positively to publicly known news. Further analysis revealed that the percentage discount of the subscription price over that of the theoretical ex-rights price was approximately 27.11% thereby re-establishing that rights issues, in order that they may be attractive to both existing shareholders and potential investors, should always be priced at discount from that of the market. Subsequently upon going ex-rights it was found that for most rights issues ( i.e. 61.5%) the actual ex-rights price corrected to approximately, on the average, 3.54% over that of the theoretical ex-rights price. These findings as set out above reconfirms that the Singapore Market is fairly efficient and that rights issues are particularly beneficial to both existing shareholders and potential investors.